2021
DOI: 10.5603/pjnns.a2021.0040
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular dysautonomia and cognition in Parkinson’s Disease — a possible relationship

Abstract: Dementia in advanced Parkinson's Disease (PD) is a fatal milestone resulting in reduced life expectancy and nursing home placement. Cognitive impairment and cardiovascular dysautonomia are common and debilitating non-motor symptoms that frequently coexist in PD since the early stages and progress in subsequent years.In particular, blood pressure (BP) abnormalities, including orthostatic hypotension (OH), supine hypertension (SH) and the loss of nocturnal BP fall (non-dipping) in PD have been associated with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Rapid Eye Movement Behaviour Disorder (RBD), a feature commonly associated with synucleinopathies, is one of the sleep abnormalities found in tauopathic parkinsonian syndromes [38][39][40][41][42][43]. Extended research has revealed that abnormalities such as RBD, which have been primarily described in synucleinopathies, have also been found to be present in PSPS and CBS.…”
Section: Sleep Disturbances In Progressive Supranuclear Palsymentioning
confidence: 99%
“…Rapid Eye Movement Behaviour Disorder (RBD), a feature commonly associated with synucleinopathies, is one of the sleep abnormalities found in tauopathic parkinsonian syndromes [38][39][40][41][42][43]. Extended research has revealed that abnormalities such as RBD, which have been primarily described in synucleinopathies, have also been found to be present in PSPS and CBS.…”
Section: Sleep Disturbances In Progressive Supranuclear Palsymentioning
confidence: 99%
“…In general, high HRV is regarded as an index of cardiovascular health [18]. Moreover, low HRV parameters are related to diverse psychiatric illnesses including major depressive disorder [19], bipolar disorder [20], anxiety disorder [21], schizophrenia [22] and Parkinson's Disease (PD) [23,24]. PLMS are frequently observed in individuals with PD, and are often accompanied by dysautonomia and cognitive impairment, which are among the non-motor symptoms associated with PD [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low HRV parameters are related to diverse psychiatric illnesses including major depressive disorder [19], bipolar disorder [20], anxiety disorder [21], schizophrenia [22] and Parkinson's Disease (PD) [23,24]. PLMS are frequently observed in individuals with PD, and are often accompanied by dysautonomia and cognitive impairment, which are among the non-motor symptoms associated with PD [24,25]. Cardiovascular ANS dysautonomia in PD involve abnormalities such as decreased HRV and impaired baroreflex sensitivity which may contribute to the increased risk of cardiovascular events in individuals with PD [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disrupted insulin signalling in the brain, apart from the loss of its physiological neuroprotective action, is supposed to decrease synaptic plasticity and affect cognition [1,26]. Since orthostatic hypotension is one of the factors thought to contribute to cognitive decline in PD [27], a possible deleterious effect of DM is easy to predict: autonomic dysfunction, resulting from α-synuclein pathology in both peripheral and central autonomic nervous system in the course of PD, may be further aggravated by autonomic neuropathy, a common but underdiagnosed complication of DM [28].…”
Section: Introductionmentioning
confidence: 99%